Legal Implications of Separating National And Regional Elections On The Terms of Office Of Regional Heads : An Analysis of Constitutional Court Decision No. 135/PUU-XXII/2024 - Arman Maulana Rachman; Alma Fauziah; Ahmad Fauzi (Ell Publication & Research Center for International Development Studies, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024, pronounced on June 26, 2025, represents a constitutional milestone that fundamentally alters Indonesia's electoral design. The Court declared the concurrent election provisions in Article 167(3) and Article 347(1) of Law Number 7 of 2017 and Article 3(1) of Law Number 8 of 2015 conditionally unconstitutional, mandating a separation between National Elections (electing DPR, DPD, and President/Vice President members) and Regional Elections (electing DPRD members and regional heads). Regional Elections must be held at least 2 years and at most 2 years and 6 months after the inauguration of National Election results, beginning from the 2029 elections. The direct consequence of this decision is a transitional period that implies adjustments—extension or curtailment—of the terms of office of regional heads and DPRD members elected in the 2024 elections. This article analyzes the juridical implications of the decision on regional heads' terms of office using the Theory of Constitutionalism and the Theory of Legal Certainty. The research employs a normative method with statutory and case approaches. The findings indicate that this decision contains constitutional engineering that delegates authority to the legislature to regulate the transitional period, while simultaneously creating legal uncertainty that must urgently be addressed through comprehensive legislation.